Two wheels good the history and mystery of the bicycle - Rosen, Jody (Crown, 2023)
The bicycle is a vestige of the Victorian era, seemingly out of pace with our age of smartphones and ridesharing apps and driverless cars. Yet we live on a bicycle planet. Across the world, more people travel by bicycle than by any other form of transportation. Almost anyone can learn to ride a bike-and nearly everyone does. In Two Wheels Good, writer and critic Jody Rosen reshapes our understanding of this ubiquitous machine, an ever-present force in humanity's life and dreamlife-and a flashpoint in culture wars-for more for than two hundred years. Combining history, reportage, travelogue, and memoir, Rosen sweeps across centuries and around the globe, unfolding the bicycle's saga from its invention in 1817 to its present-day renaissance as a "green machine," an emblem of sustainability in a world afflicted by pandemic and climate change. Readers meet unforgettable characters: feminist rebels who steered bikes to the barricades in the 1890s, a prospector who pedaled across the frozen Yukon to join the Klondike gold rush, a Bhutanese king who races mountain bikes in the Himalayas, a cycle rickshaw driver who navigates the seething streets of the world's fastest-growing megacity, astronauts who ride a floating bicycle in zero gravity aboard the International Space Station"--